(untitled) (Journal of Economic Research & Business Administration, 2024)
The COVID-19 pandemic has not only fundamentally transformed organizational practices, but leading to an unprecedented shift toward remote work at the same time. This study focuses on understanding the relationship between remote work and employee motivation, which has attracted increased interests in the post-pandemic era. The purpose of this study is to conduct a bibliometric review of the literature, highlighting key research trends, central themes, and influential contributions in this field. Based on 50 publications retrieved from the Web of Science Core Collection, the analysis employs mapped publication trends, citation structures, keyword co-occurrence networks, and leading countries by using scientific research tools include VOSviewer and CiteSpace. The findings reveal significant research clusters addressing psychological well-being, job satisfaction, autonomy, and the integration of digital tools in modern organizational practices. Notably, the results show an exponential growth in academic interest beginning in 2020, driven by the global adoption of remote work and its implications for employee motivation. The analysis contributes to the existing theoretical system by providing a comprehensive overview of research developments in remote work and employee motivation. The analysis identifies three potential future research directions: exploring the dynamic evolution of motivational needs in remote work environments, assessing the long-term impacts of remote work on mental health and organizational outcomes, and evaluating the effectiveness of new motivational strategies, such as autonomy support, in mitigating employee burnout. The significance of the research is informing organizational leaders and policymakers about emerging trends and effective motivational strategies, helping them to enable better adaptation to remote and hybrid work environments in the future. Key words: employee motivation, remote work, bibliometric analysis.